Community-Acquired Pneumonia: Genomics, Epigenomics, Transcriptomics, Proteomics, and Metabolomics - Waterer, Grant W. (Seminars in Respiratory and Critical Care Medicine, 2012)
Community-acquired pneumonia remains a significant health problem with very little progress having been made over the past 2 to 3 decades. Recent technological advances have opened up whole new avenues of exploration in the fields of genomics, epigenomics, transcriptomics, proteomics, and metabolomics. Although data in pneumonia are relatively scant with the exception of genomics due to the early stages of the science, some intriguing insights and clear avenues of application are already emerging. This review discusses recent studies in pneumonia using these new approaches as well as relevant research in sepsis and other diseases. Current and potential future uses of these platforms are discussed, and both key findings and key barriers to further progress are highlighted.
Keywords: pneumonia; genomics; proteomics; metabolomics; epigenomics